Survey under-coverage of top incomes and estimation of inequality: What is the role of the UK's SPI adjustment? - Richard V. Burkhauser; Nicolas Hérault; Stephen P. Jenkins; Roger Wilkins (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Survey under-coverage of top incomes leads to bias in survey-based estimates of overall income inequality. Using income tax record data in combination with survey data is a potential approach to address the problem; we consider here the UK's pioneering "SPI adjustment" method that implements this idea. Since 1992, the principal income distribution series (reported annually in Households Below Average Income) has been based on household survey data in which the incomes of a small number of "very rich" individuals are adjusted using information from "very rich" individuals in personal income tax return data. We explain what the procedure involves, reveal the extent to which it addresses survey under-coverage of top incomes, and show how it affects estimates of overall income inequality. More generally, we assess whether the SPI adjustment is fit for purpose and consider whether variants of it could be employed by other countries.
Keywords: D31; C81; 330; inequality; income inequality; survey under-coverage; SPI adjustment; top incomes; tax return data; survey data; Einkommensverteilung; Datenerhebung; Einkommensstatistik; Schätztheorie; Großbritannien